Legal limitations for nurse prescribers in Primary Health Care - N. Geyer (AOSIS, 1998)
The nurse plays an important role in the delivery of primary health care services in South Africa. The primary purpose is to provide the public with access to safe competent basic health care and to achieve this, the nurse should be empowered to practice within legal and ethical boundaries. This paper explores and describes the limitations imposed by legislation on the nurse's ability to prescribe treatment in the primary health care field. The focus is mainly on the Nursing Act, the Pharmacy Act and the Medicines and Related Substances Control Act which highlights a number of limitations. It is concluded that empowerment of the nurse should not only include addressing the legal boundaries for practice, but also education and training opportunities to equip them with the expert knowledge and skills that they need to render a quality health care service.